Africa struggles with soaring food prices - Michael Fleshman (Africa Renewal, 2008)
The protests against soaring food prices that swept dozens of countries around the world earlier this year have shaken governments and international aid agencies. They have also prompted a flurry of activity to lower the cost of basic staples and expand farm production.